Crystal Structure of Bis(2-methoxy-6-((Z)-(p-tolylimino)methyl)phenoxy)palladium - Kassim, K; Kahar, MAM; Yamin, BM; Manan, MAFA; Yusof, MSM (Japan Soc Analytical Chemistry, 2024)
The structure of bis(2-methoxy-6-((Z)-(p-tolylimino)methyl)phenoxy)palladium crystallized in a monoclinic system and was characterized thus: P2(1)/c, a = 13.0221(14), b = 11.6615(13), c = 8.4898(9)angstrom, beta = 97.327(4)degrees, Z = 2, V = 1278.7(2)angstrom(3). The crystal structure was solved by direct methods and refined by full-matrix least-squares on F2 to final values of R1 = 0.0349 [I > 2 sigma(I)] and wR2 = 0.0824. The molecules have two-fold symmetry about the centre Pd1 atom. Two ligands were coordinated to the Pd1 atom via oxygen and nitrogen atoms in a bidentate manner to form a square-planar geometrical structure.